DOP086 Low FODMAP diet improves functional-like gastrointestinal symptoms but reduces bifidobacteria and faecalibacterium prausnitzii in Quiescent inflammatory bowel disease: a randomised controlled trial and metagenomic analysis. (16th January 2018) - Cox, S; Stagg, A; Fromentin, S; Ehrlich, D; McCarthy, N; Galleron, N; Levenez, F; Lomer, M; Lindsay, J; Irving, P; Whelan, K
Abstract: Background: Many patients with quiescent inflammatory bowel disease (IBD) also experience functional-like gastrointestinal (GI) symptoms. Dietary restriction of fermentable carbohydrates (low FODMAP diet) improves GI symptoms in quiescent IBD in uncontrolled trials but there are no placebo-controlled trials to confirm this. We aimed to perform a randomised, placebo-controlled trial to assess the effects of a low FODMAP diet on GI symptoms, intestinal microbiota, inflammatory markers and circulating gut-tropic (α4β7+) T cells in patients with quiescent IBD. Methods: Patients with Crohn's disease or ulcerative colitis were included. Quiescent IBD was defined as: (1) Physician Global Assessment, (2) faecal calprotectin [FC] <250 µg/g and (3) CRP <10 mg/l. Suitable patients fulfilled the Rome III criteria for IBS, functional bloating or functional diarrhoea, and were naïve to the low FODMAP diet. Participants were randomised to low FODMAP or placebo (sham) dietary advice for 4 weeks. At baseline and end of trial, GI symptoms and stool output were measured using validated questionnaires and FC was measured using ELISA. Faecal microbiota were characterised using metagenomic sequencing and α4β7+ T-cell populations quantified using multi-colour flow cytometry. End of trial data were compared between the diets in an intention-to-treat fashion using analysis of covariance adjusting for baseline values. Results: Fifty-two patients were randomised (27 low FODMAP diet, 25 sham diet). At the end of trial, more patients reported adequate relief of GI symptoms following the low FODMAP diet (14/27, 52%) than the sham diet (4/25, 16%) ( p = 0.007). Total IBS Severity Scoring System score decreased by 67 points (SD 78) during the low FODMAP diet and 34 points (SD 50) during the sham diet ( p = 0.075). Daily stool frequency was lower following the low FODMAP diet (1.7 SD 0.5) than the sham diet (2.1 SD 0.5) ( p = 0.012). There was no difference in bacterial gene richness ( p = 0.620) between diet groups at end of trial, however the relative abundance of Bifidobacterium longum ( p = 0.003) and Bifidobacterium adolescentis ( p = 0.015) were significantly lower following the low FODMAP diet compared with sham diet. There was a decline in Faecalibacterium prausnitzii SL3/3-M21/2 ( p = 0.029) and Faecalibacterium prausnitzii KLE1255 ( p = 0.006) between baseline and end of trial in the low FODMAP diet group only. There was no difference in FC or proportions of α4β7+ T cells between groups at end of trial. Conclusions: The low FODMAP diet improved functional-like GI symptoms in patients with quiescent IBD but reduced immunoregulatory species of the intestinal microbiota, though did not impact on inflammatory markers or α4β7+ blood T-cell numbers.